Analysis of Technical Planning Principles for Partial Underground Cabling in Meshed Extra-High Voltage Grids - Veerashekar, Kishan; Siebels, Carsten; La Seta, Piergiovanni; Fuchs, Bernhard (Jicable'15 - 9th International Conference on Insulated Power Cables, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.IE.leen.analys

Bewertung der transienten Stabilität von vernetzten autonomen hybriden Mikronetzen - Veerashekar, Kishan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)

Frequency Regulation in Transmission Grids Using Virtually Interconnected Battery Storage Systems - Veerashekar, Kishan; Weiß, Sebastian; Luther, Matthias (International CIGRÉ Symposium, 2017)

Impact of Distributed Battery Energy Storage Systems on Low Voltage Grids with High Amount of Photovoltaics - Veerashekar, Kishan; La Seta, Piergiovanni; Luther, Matthias (International ETG Congress 2015 - Die Energiewende, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.IE.leen.impact

Investigation, modeling and simulation of redox-flow, lithium-ion and lead-acid battery systems for home storage applications - Schlund, Jonas; Betzin, Christopher; Wolfschmidt, Holger; Veerashekar, Kishan; Luther, Matthias (Proceedings of the 11th International Renewable Energy Storage Conference (IRES 2017), 2017)
In this paper three different storage system solutions were investigated, modeled and simulated in order to describe their operational behavior and benefits for home storage applications. A redox-flow, a lithium-ion and a lead-acid battery were connected via converters with the grid. Their total performance was analyzed and correlations between the efficiency and the power as well as the performance limits and the state of charge were determined by the means of test runs. The real capacity and the losses of all single components were ascertained in the laboratory. Hence, the results of the measurements represent a quantified assessment of the state-of-the art of storage technologies. On the basis of the test results mathematical models of the storage systems were developed. They reproduce the influences of the different components separately and are capable of being parameterized and scaled within certain limits of power and energy content. The models were validated by the means of a five-day experiment and reached an accuracy of prediction with a mistake of an upper bound of 3.3 % in average for the three different systems. The operation of the storage systems in a private household with a photovoltaic system was simulated over one year with the developed models. The average efficiency factors reach approximately 53 % (redox-flow), 72 % (lithiumion) and 67 % (lead acid). The simulations showed that the self-sufficiency-rate and the self-consumption-rate can be improved to 60 % and 45 % respectively at the given setup of a 5 kWp photovoltaic system and a usable battery capacity of 8 kW
Keywords: energy storage; pv home storage; battery; redox-flow; lithium-ion

Kleinsignalstabilität von vernetzten autonomen Mikronetzen - Veerashekar, Kishan; Flick, Matthias; Luther, Matthias (ETG-Kongress 2019 - Das Gesamtsystem im Fokus der Energiewende, 2019)
Clustering of stand-alone microgrids (μgrids) provides advantages in terms of cost efficiency and security of supply. Exemplary island μgrids comprising diesel-based generators were modelled and validated to perform small-signal stability analyses at different operating points as well as in island and cluster mode. According to the results, the occurring modes have much higher frequencies (up to 10 Hz) compared to those in transmission systems. All significant eigenvalues can be classified as controller type and no inter-area eigenvalues are noticed. The clustering of the analysed μgrids does not have a negative impact on the small-signal stability. Further, it can be concluded that a less damping ratio (e.g. 1-2 %) – due to very small damping time constants – is not critical in μgrids.
CRIS-Team Scopus Importer:2021-04-20

Large Signal Stability Analysis in Clustering of Microgrids Using A Hybrid Method - Veerashekar, Kishan; Göpel, Alexander; Luther, Matthias (MEDPOWER - 11th Mediterranean Conference on Power Generation, Transmission, Distribution and Energy Conversion, 2018)

Modelling and Transient Stability Analysis of Interconnected Autonomous Hybrid Microgrids - Veerashekar, Kishan; Eichner, S; Luther, Matthias (13th IEEE PES PowerTech Conference, 2019)

Probabilistic Load-Flow Analyses in Distribution Grids with Battery Storage Systems Providing Frequency Containment Reserve - Veerashekar, Kishan; Mitterreiter, Christian; Luther, Matthias (International CIGRÉ Symposium, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IE.leen.probab

Qualitative and Quantitative Transient Stability Assessment of Stand‐Alone Hybrid Microgrids in a Cluster Environment - Veerashekar, Kishan; Askan, Halil; Luther, Matthias (Energies, 2020)

Quantitative transient stability assessment in microgrids combining both time-domain simulations and energy function analysis - Veerashekar, Kishan; Schühlein, P; Luther, Matthias (International Journal of Electrical Power & Energy Systems, 2020)

StroMiS - Studie zur technisch-wirtschaftlichen Analyse der Stromerzeugung aus Mikrokraftwerken in Serienfertigung - Scholz, Michael; Kühl, Alexander; Höft, Annika; Landgraf, Maximilian; Schneider, Michael; Böhm, Ralf; Badel, Gregor; Lothes, Gerald; Angerer, Kerstin; Hohmann, Andrea; Simon, Peter; Konwitschny, Fabian; et al. (2019)

SWARM – Successful Provision of Frequency Containment Reserve with Distibuted Energy Storage Systems - Leepa, Claudia; Kufner, Annika; Mehl, Simon; Steber, David; Veerashekar, Kishan; Sigert, Ingo; Götz, Kornelia; German, Reinhard; Grimm, Veronika; Luther, Matthias (Conference Presentations and Materials of the "10th International Renewable Energy Storage Conference" (IRES 2016), Düsseldorf/Germany, 15-17 March 2015, 2016)
In July 2015, a network of 65 virtually connected distributed energy storage systems (ESS) with a total nominal power of 1 MW – so-called SWARM – was successfully prequalified for frequency containment reserve (FCR) provision within the balancing area of TenneT TSO GmbH in Germany. ESS were installed in private households possessing a rooftop photovoltaic system. In contrast to ordinary ESS available in the market for home application, SWARM-ESS do not only increase the households’ self-consumption, but they work as a virtual mass storage. Coordinated by an automated control center, SWARM is able to provide FCR by responding proportionally to frequency deviations of up to 200 mHz within few seconds and thus, contributes to stabilizing the grid. Hence, SWARM represents a systematic decentralized approach for meeting one of the main challenges of the energy transition in Germany. Roll out and operation of SWARM are conducted by a cooperation between N-ERGIE Aktiengesellschaft and Caterva GmbH. The project’s research activities are supported by groups of the Friedrich-Alexander-University addressing both, economic and technical issues. From an economic perspective, the identification of determinants of individual decision-making in exposure to novel technology is emphasized. As far as technical issues are concerned, the effects of distributed ESS on the grid, the provision of FCR by a virtual mass storage as well as the operational behavior of SWARM are analyzed. To this end, a stochastic and hybrid simulation model is developed to generate time series of all power flows within each house as well as the FCR provided. These time series are used for load flow calculations to identify the influence of ESS on the local distribution grid. All in all, this paper gives an overview of first experiences in the operation of SWARM as well as of research results from the different discipline
Keywords: distributed battery energy storage systems; frequency containment reserve

The micro-hybrid method to assess transient stability quantitatively in pooled off-grid microgrids - Veerashekar, Kishan; Flick, M; Luther, Matthias (International Journal of Electrical Power & Energy Systems, 2020)

Transient Stability of Hybrid Stand-alone Microgrids Considering the DC-Side of Photovoltaics - Veerashekar, Kishan; Bichlmaier, A; Luther, Matthias (4th International Hybrid Power Systems Workshop, 2019)

Virtueller Großspeicher zur Erbringung von Primärregelleistung – Pilotprojekt SWARM - German, Reinhard; Götz, Kornelia; Grimm, Veronika; Kufner, Annika; Leepa, Claudia; Luther, Matthias; Mehl, Simon; Sigert, Ingo; Steber, David; Veerashekar, Kishan (OTTI-Konferenz „Zukünftige Stromnetze für Erneuerbare Energien“, 2017)
Keywords: Virtueller Großsspeicher; dezentral; vernetzt; Primärregelleistung